Cardiopulmonary nematodes of wild carnivores from Denmark: Do they serve as reservoir hosts for infections in domestic animals?. (December 2020) - Lemming, Louise; Jørgensen, Ann Cholewa; Nielsen, Linette Buxbom; Nielsen, Stine Thorsø; Mejer, Helena; Chriél, Mariann; Petersen, Heidi Huus
Abstract: The cardiopulmonary nematodes Angiostrongylus vasorum, Crenosoma vulpis, Capillaria aerophila and Aelurostrongylus abstrusus, are a cause of concern in the scientific and veterinary community, potentially causing significant disease in domestic animals. To investigate the potential of wild carnivores as reservoir hosts to these parasites, a total of 1041 animals from seven regions of Denmark were sampled: 476 raccoon dogs ( Nyctereutes procyonoides ), 367 red foxes ( Vulpes vulpes ), 123 American mink ( Neovison vison ), 31 beech martens ( Martes foina ), 30 Eurasian otters ( Lutra lutra ) and 14 polecats ( Mustela putorius ). Hearts and lungs were collected and examined for cardiopulmonary parasites. Capillaria aerophila was identified using morphology, whereas A. vasorum and C. vulpis were identified by a duplex real-time PCR, and A. abstrusus by conventional PCR. This is the first Danish report of A. vasorum and C. vulpis infections in raccoon dogs, mink and polecats, and of C. aerophila in raccoon dogs and beech martens. In addition, this is the first time A. vasorum and C. vulpis have been identified in wild animals from the island of Bornholm, just as it is the first report of C. vulpis in American mink, and C. vulpis and A. vasorum in polecats in Europe. The prevalence of A. vasorum appears to have increased in red foxes in Denmark compared to previous studies, while C. vulpis and C. aerophila prevalences are lower. Our data show that several wild carnivores can serve as reservoir hosts for A. vasorum, C. vulpis and C. aerophila in Denmark, and that A. vasorum appears more abundant than previously reported. It is speculated that the A. vasorum increase might relate to increased snail abundance, which may be due to a rise in mean yearly temperatures in Denmark. Graphical abstract: Image 1 Highlights: The first report of C. vulpis in American mink. The first report of C. vulpis and A. vasorum in polecats. The first report of A. vasorum in raccoon dogs, mink, and polecats from Denmark. The first report of C. vulpis in raccoon dogs, mink, and polecats from Denmark. The first report of C. aerophila in raccoon dogs and beech martens from Denmark.